Nanoscale Organisation of Ryanodine Receptors and Junctophilin-2 in the Failing Human Heart - Hou, Yufeng; Bai, Jizhong; Shen, Xin; de Langen, Oscar; Li, Amy; Lal, Sean; dos Remedios, Cristobal G.; Baddeley, David; Ruygrok, Peter N.; Soeller, Christian; Crossman, David J. (Frontiers in Physiology, 2021)
The disrupted organisation of the ryanodine receptors (RyR) and junctophilin (JPH) is thought to underpin the transverse tubule (t-tubule) remodelling in a failing heart. Here, we assessed the nanoscale organisation of these two key proteins in the failing human heart. Recently, an advanced feature of the t-tubule remodelling identified large flattened t-tubules called t-sheets, that were several microns wide. Previously, we reported that in the failing heart, the dilated t-tubules up to 1 μm wide had increased collagen, and we hypothesised that the t-sheets would also be associated with collagen deposits. Direct stochastic optical reconstruction microscopy (dSTORM), confocal microscopy, and western blotting were used to evaluate the cellular distribution of excitation-contraction structures in the cardiac myocytes from patients with idiopathic dilated cardiomyopathy (IDCM) compared to myocytes from the non-failing (NF) human heart. The dSTORM imaging of RyR and JPH found no difference in the colocalisation between IDCM and NF myocytes, but there was a higher colocalisation at the t-tubule and sarcolemma compared to the corbular regions. Western blots revealed no change in the JPH expression but did identify a 50% downregulation of RyR (p = 0.02). The dSTORM imaging revealed a trend for the smaller t-tubular RyR clusters ( 24%) and reduced the t-tubular RyR cluster density ( 35%) that resulted in a 50% reduction of t-tubular RyR tetramers in the IDCM myocytes (p < 0.01). Confocal microscopy identified the t-sheets in all the IDCM hearts examined and found that they are associated with the reticular collagen fibres within the lumen. However, the size and density of the RyR clusters were similar in the myocyte regions associated with t-sheets and t-tubules. T-tubule remodelling is associated with a reduced RyR expression that may contribute to the reduced excitation-contraction coupling in the failing human heart.